Ruptured mycotic abdominal aortic aneurysm in the setting of an adjacent perinephric abscess - Schaal, Alexandar; Hassanesfahani, Maryam; Mutyala, Manikyam (International Surgery Journal, 2024)
Arterial aneurysms are most commonly present due to progressive vessel wall injury. They may then act as a nidus for bacterial seeding that can lead to the formation of a mycotic aneurysm in 2.5% of all abdominal aneurysms, which is associated with high mortality. Management of mycotic aortic aneurysm has been challenging always. Here we present a rare case of a ruptured mycotic aneurysm secondary to contiguous extension of a perinephric abscess. The patient required emergent surgery and underwent reconstruction of the aorta using a Dacron graft with a good 18 months outcome.